Tinjauan Yuridis Kawin Gantung Masyarakat Melayu Desa Dahari Indah Kecamatan Talawi Kabupaten Batu Bara - Asyrofulmuttaqin, Asyrofulmuttaqin; Nasution, Muhammad Syukri Albani (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Marriage is a sacred matter, the pillars and conditions must be fulfilled. In the Indonesian context, marriage must be registered and in an orderly administration. There are other matters that are very important for the Malay community in Batu Bara Regency, when a marriage (akad nikah) takes place, while the walimatul `urs has not been carried out, the bride and groom cannot live together, the rights and obligations of each cannot be carried out until walimatul `urs urs is held, this marriage is known as the "Kawin Gantung". This study wants to analyze the kawin gantungtradition, and a juridical review of the hanging marriage custom practiced in Dahari Indah Village, Talawi District, Batu Bara Regency. This type of research is qualitative, with a juridical-empirical approach, the primary sources consist of observations and interview results as well as laws and regulations in Indonesia regarding marriage. Data collection techniques were carried out by means of observation and interviews. The results of the study found that hanging marriage practiced by the community is a tradition that has long existed, and is part of local wisdom. It is known that the custom of kawin gantung does not conflict with the laws and regulations in Indonesia, and also in the Syafi`i school of law. Kawin gantung have a noble purpose, so that young couples do not fall into adultery, so that the marriage contract is permitted beforehand, even though they are not allowed to live in the same house, and have not been burdened with household duties and obligations. The implementation of a hanging marriage must have the agreement of both partners and both parties from the partner's family, if the couple is forced and not happy, then the kawin gantung is not carried out.